Rubberlike Elasticity : a Molecular Primer. - Erman, Burak; Bokobza, Liliane (Cambridge University Press, 2007)
Elastomers and rubberlike materials form a critical component in diverse applications that range from tyres to biomimetics and are used in chemical, biomedical, mechanical and electrical engineering. This updated and expanded edition provides an elementary introduction to the physical and molecular concepts governing elastic behaviour, with a particular focus on elastomers. The coverage of fundamental principles has been greatly extended and fully revised, with analogies to more familiar systems such as gases, producing an engaging approach to these phenomena. Dedicated chapters on novel uses of elastomers, covering bioelastomers, filled elastomers and liquid crystalline elastomers, illustrate the established and emerging applications at the forefront of physical science. With a list of experiments and demonstrations, problem sets and solutions, this is a self-contained introduction to the topic for graduate students, researchers and industrialists working in the applied fields of physics and chemistry, polymer science and engineering.